2002
DOI: 10.1111/j.1095-8649.2002.tb02465.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and interannual variation in fish assemblages of northern temperate rocky subtidal habitats

Abstract: Fish assemblages on two inshore rocky subtidal sites on the west coast of Scotland, were studied using diver visual surveys on a monthly basis between September 1995 and December 1999. A total of 17 689 fishes and 26 species were recorded from the two sites, Saulmore Point (056 27 N; 005 24 W) near Oban and Davy's Rock (055 46 N; 004 53 W) on the Isle of Great Cumbrae. The gobiid Thorogobius eppiphiatus, dominated the Saulmore Point site; six fish species accounted for >93% of total abundance at that site. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 36 publications
3
22
1
Order By: Relevance
“…None of these two events were found either during the survey or in our analyses. The highlighted fish seasonal changes had already been observed in this region (Magill and Sayer 2002;Valle et al 2007).…”
Section: Discussionmentioning
confidence: 82%
“…None of these two events were found either during the survey or in our analyses. The highlighted fish seasonal changes had already been observed in this region (Magill and Sayer 2002;Valle et al 2007).…”
Section: Discussionmentioning
confidence: 82%
“…In the North Atlantic and Mediterranean several studies have been done on rocky coastal ¢sh assemblages (Jansson et al, 1985;Minchin, 1987;Miniconi et al, 1990;Falcon et al, 1993;MacPherson, 1994;Ren‹ ones et al, 1997;La Mesa & Vacchi, 1999;Gonc°alves et al, 2002;Magill & Sayer, 2002;La Mesa et al, 2004;Ordines et al, 2005). Most of these studies used traditional visual census methods to assess the whole ¢sh assemblage, including cryptobenthic ¢sh.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the temporal dynamics of coastal ¢sh assemblages in temperate areas have shown strong seasonal and inter-annual variations in density for some species (Janson et al, 1985;Costello, 1992;Wilkins & Myers, 1992;Magill & Sayer, 2002). Temporal dynamics of ¢sh populations have broadly been related to the input of recruits (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This could explain the signiWcant interaction between time and treatment in this study as the recruitment of juvenile Wsh in these waters occurs during the summer month and movement by Wsh to deeper waters takes place during the winter. Seasonal changes in abundance of observed Wsh species due to migration has been reported from both the North Sea and the Baltic Sea (Thorman 1986;Magill and Sayer 2002;Pihl and Wennhage 2002;Wilhelmsson et al 2006b). …”
Section: Fish Assemblagementioning
confidence: 99%